The Effect Of Brand Trust, Brand Awareness, And Brand Positioning On The Purchase Decision Of Honda Brand Motorcycle In Students Of Muhammadiyah Ponorogo University - Gandhi Gumelar; Titi Rapini; Naning Kristiyana (Universitas Medan Area, 2023)
Marketing management is the science of selecting target markets and achieving and retaining them by creating and delivering superior consumer value, thus creating purchasing decisions for consumers. This study aims to find out how the influence of Brand Trust, Brand Awareness, and Brand Positioning on the Purchase Decisions of Honda Brand Motorcycles in Muhammadiyah University Ponorogo Students partially or simultaneously. The sample is a consumer of a Honda brand motorbike at Muhammadiyah University Ponorogo students who make purchases; sampling uses an accidental sampling technique and a sample of 96 respondents. The testing stages used in this study were instrument testing, multiple linear regression analysis, coefficient of determination test, and hypothesis testing. This research produces a partial test (t) which is as follows Brand Trust (X1) = 0.004, Brand Awareness (X2) = 0.001, and Brand Positioning (X3) = 0.000, while the test results (F) show a significant level of 0.000. Brand Trust, Brand Awareness, and Brand Positioning partially or simultaneously positively and significantly influence the Purchase Decision of Honda Brand Motorcycles at Muhammadiyah University Ponorogo Students.